Research and analysis of efficiency indicators of critical infrastructures in the communication system - Ibrаhimov, Bayram; Hasanov, Arif; Hashimov, Elshan (Національний технічний університет "Харківський політехнічний інститут", 2024)
The efficiency indicators of the functioning critical information infrastructures in the communication system are analyzed based on the architectural concept of future networks. The object of the study is hardware and software complexes critical information infrastructures for special purposes. Critical information infrastructure represents information and telecommunication communication systems, the maintenance, reliability and security which are necessary for the safe operation special-purpose enterprises. In order to avoid the occurrence of various security and reliability incidents, the studied critical infrastructures communication systems require constant analysis and updating operating rules. The subject of the research is a method for calculating quality indicators of the functioning of critical information infrastructures in communication systems. In this work, using the example of a communication system based on modern technologies, the sequence of actions for analyzing threats to the security of a critical information infrastructure facility is considered. The purpose of the study is to develop a new approach for creating methods for calculating indicators of efficiency, reliability and information security systems. Based on the analysis of the work, a method for calculating efficiency indicators critical information infrastructures of communication systems is proposed and important analytical expressions for further research are obtained. As a result of the study, the main conclusions of the study were obtained, which can be implemented and used in critical infrastructures of communication systems to calculate the quality of functioning public computer and telecommunication systems.

На основі архітектурної концепції майбутніх мереж проаналізовано показники ефективності функціонування критичних інформаційних інфраструктур у системі зв’язку. Об’єктом дослідженняє апаратно-програмні комплекси критичних інформаційних інфраструктур спеціального призначення. Критична інформаційна інфраструктура являє собою інформаційно-телекомунікаційні системи зв'язку, технічне обслуговування, надійність і безпека яких необхідні для безпечної роботи підприємств спеціального призначення. Щоб уникнути виникнення різноманітних інцидентів безпеки та надійності, системи зв’язку досліджуваних критичних інфраструктур вимагають постійного аналізу та оновлення правил роботи. Предметом дослідженняє метод розрахунку показників якості функціонування критичних інформаційних інфраструктур систем зв’язку. У даній роботі на прикладі системи зв’язку на основі сучасних технологій розглянуто послідовність дій для аналізу загроз безпеці об’єкта критичної інформаційної інфраструктури. Метою дослідженняє розробка нового підходудо створення методів розрахунку показників ефективності, надійності та інформаційної безпеки систем. Результати. На основі аналізу роботи запропоновано метод розрахунку показників ефективності критичних інформаційних інфраструктур систем зв’язку та отримано важливі аналітичні вирази для подальших досліджень. В результаті проведеного дослідження отримано основні висновки дослідження, які можуть бути реалізовані та використані в критичних інфраструктурах систем зв’язку для розрахунку якості функціонування загальнодоступних комп’ютерних та телекомунікаційних систем.
Дослідження та аналіз показників ефективності критичних інфраструктур у системі зв'язку
Keywords: threat probability; risk; information security system; vulnerability probability; unctioning public computer; reliability; система захисту інформації; ймовірність уразливості; критичні інформаційні інфраструктури; загроза; надійність; показники якості